2017
DOI: 10.1186/s12898-017-0156-6
|View full text |Cite
|
Sign up to set email alerts
|

Genetic diversity and structure related to expansion history and habitat isolation: stone marten populating rural–urban habitats

Abstract: BackgroundPopulation genetic diversity and structure are determined by past and current evolutionary processes, among which spatially limited dispersal, genetic drift, and shifts in species distribution boundaries have major effects. In most wildlife species, environmental modifications by humans often lead to contraction of species’ ranges and/or limit their dispersal by acting as environmental barriers. However, in species well adapted to anthropogenic habitat or open landscapes, human induced environmental … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
20
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 27 publications
(22 citation statements)
references
References 81 publications
1
20
0
1
Order By: Relevance
“…As recorded for both pine martens (Balestrieri et al 2016a) and otters (Vergara et al 2014), most individuals were related to each other, suggesting rapid population renewal and that dispersion occurs on relatively short distances. Heterozygosity matched with average values for the pine marten in continental Europe (min-max 0.56-0.7; Kyle et al 2003;Pertoldi et al 2008), while was slightly higher than that reported for the stone marten (Iberian Peninsula: Ho = 0.49, Vergara et al 2015; Eastern France: Ho = 0.55, Larroque et al 2016; Poland: Ho = 0.52, Wereszczuk et al 2017).…”
Section: Discussionsupporting
confidence: 70%
“…As recorded for both pine martens (Balestrieri et al 2016a) and otters (Vergara et al 2014), most individuals were related to each other, suggesting rapid population renewal and that dispersion occurs on relatively short distances. Heterozygosity matched with average values for the pine marten in continental Europe (min-max 0.56-0.7; Kyle et al 2003;Pertoldi et al 2008), while was slightly higher than that reported for the stone marten (Iberian Peninsula: Ho = 0.49, Vergara et al 2015; Eastern France: Ho = 0.55, Larroque et al 2016; Poland: Ho = 0.52, Wereszczuk et al 2017).…”
Section: Discussionsupporting
confidence: 70%
“…However, the stone marten has regional intraspecific differences in habitat choice, being less associated with human settlements in Southern than in Central Europe (Sacchi and Meriggi 1995). The pine marten density may decline, but the stone marten may accelerate expiation due to habitat loss, mainly deforestation (Caryl et al 2012, Wereszczuk et al 2017). Thus, both species' current distribution may have been shaped by habitat preferences and anthropogenic factors in different ways (Proulx et al 2004).…”
Section: Introductionmentioning
confidence: 99%
“…The stone martens’ diet does not consist of amphibians and reptiles; they mainly prey on small mammals and birds [ 68 ], which can be a potential source of infection. In NE Europe, stone martens usually occur in urban and rural areas and avoid large, continuous forest complexes [ 69 ], which limit their potential to come into contact with possible wild hosts of S. erinaceieuropaei . So far, stone martens have been considered a host for Spirometra sp.…”
Section: Discussionmentioning
confidence: 99%